The Impact of the Average Temperature, Humidity, Wind Speed, Altitude, and Population Density on Daily COVID-19 Infection Evolution - Rachid Lagtayi; Lamya Lairgi; Abdelmajid Daya; Ahmed Khouya (Medical Sciences Forum, 2021)
The aim of this study is to investigate the impact of climate conditions, altitude, and population density on daily COVID-19 infection evolution. For an average wind speed of greater than 25 km/h, the number of daily COVID-19 infections slightly decreased with a rate of 10%, while the temperature, humidity and altitude factors did not affect its evolution. Furthermore, population density strongly affects its progression with an approximate rate of 90%. Finally, we propose a mathematical model to estimate the evolution of COVID-19 infections over time by simultaneously taking into consideration the wind speed and the population density effects.